Wekk if the method posted by Joy is mere " Ad-hoc " reasoning then it's correct way to do it!
4 Answers
Joydoot ghatak
·2011-04-13 22:50:53
g(f(x)) = √sin2x = √(sin x)2
f(g(x)) = (sin √x)2.
thus, we can see clearly that..
g(x) = √x and f(x) = sin2x.
i didn't guess but mine is not so much analytical as u may want.. :(
kunl
·2011-04-13 22:53:17
in fact it is not analytical at all....but good part is that i did the same as u did :P mere "ad-hoc" reasoning [3]
Vivek @ Born this Way
·2011-04-19 04:18:37